Open-hole tensile strength of quasi-isotropic laminates - Morais, Alfredo Balacó de
In this work, a new approach is suggested for predicting the open-hole tensile strength of quasi-isotropic [0 degrees/+/-45 degrees/90 degrees](ns) laminates. The well known size dependency of the layer longitudinal tensile strength is explicitly taken into account. The interest in such an approach lies in avoiding material-dependent empirical parameters, e.g. characteristic distances, whose physical meaning is not always clear. In situ fibre strengths were estimated by using longitudinal stresses obtained from finite-element models and experimental data available in the references. The estimated size-dependent fibre strengths were found to be consistent with typical Weibull distributions. It is also worth emphasising that mixed 2D/3D finite-element models were used in this work, since the common 2D models proved to be significantly inaccurate.